(untitled) (Medico Legal Update, 2021)
Non-Hodgkin’s lymphoma (NHL) chemotherapy is cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) have hyperglycemia side effects that affect the success of chemotherapy. Improved glycemic control decreases morbidity and mortality. Determine the glycemic control changes in non-DM NHL patients before and the sixth day after the first CHOP chemotherapy. Method: Prospective longitudinal observational analytic study in the Internal Medicine Inpatient Unit Dr. Soetomo Teaching Hospital Surabaya, involved all the first CHOP chemotherapy NHL patients during November 2019-February 2020. A total of 21 patients met chemotherapy requirements and were not DM. The glycemic control check uses the hexokinase method and a glucometer (Easy Touch®). Data analysis using the Wilcoxon test was considered significant if p <0.05. Results: Total research subjects were 21 people, female domination (66.7%), mean age 49.24 ± 13.96 years, clinical stage 3 dominance (52.38%), mean HbA1C 5.75 ± 0.49%, average FBG 90.86 ± 13.13 mg/dL, the mean PPBG 114.33 ± 20.16 mg/dL. Daily blood glucose levels during chemotherapy were highest on the first day’s pre-dinner. There were significant differences in FBG and PPBG before chemotherapy and the sixth day after chemotherapy (p-values 0.032 and 0.002). The incidence of new-onset DM on the sixth day after the first CHOP chemotherapy was 2 subjects (9.53%). Conclusion: There was an increase in FBG and PPBG of NHL non-DM patients before and the sixth day after the first CHOP chemotherapy